Grindletonianism in Manuscript and Print: the Role of Josiah Collier (1595–1677). (10th March 2018) - Pickering, Oliver
Abstract: Grindletonianism, a manifestation of antinomian religious belief that attracted followers in northern England during the seventeenth century, has come down to us through the writings of Roger Brereley (1586?–1637), one-time curate of Grindleton, in Craven, and his disciple Josiah Collier (1595–1677). These writings, in both prose and verse, survive in two manuscripts in Collier's hand and, in part, in a printed book, A Bundle of Soul-Convincing, Directing and Comforting Truths (1670, 1677), of which the first edition was printed in Edinburgh for sale in Glasgow. After a brief account of Collier's life, a summary of the contents of the two manuscripts, and a description of the printed editions, the article appraises the differing contents of the manuscripts and their likely dates of compilation; discusses the textual choices and modifications that took place in the transition from manuscript to print; and considers the extent to which Collier himself may have been involved in the production of the printed volume. The conclusion is that Collier very likely revised some of the manuscript materials in an apparent effort to weaken the antinomian sentiment in order to make the doctrines more acceptable to a mainstream Puritan readership, and that he was possibly prompted to do this by his patron Jane Baildon, for whom he wrote the less outspoken of the two manuscripts. The article further considers the uncertain bibliographical status of the second, verse section of the 1670 edition of A Bundle of Soul-Convincing, Directing and Comforting Truths, which was produced separately from the first (which contains Brereley's sermons), and it ends by demonstrating that the so-called 1676 edition of the volume (Wing B4658A) is a ghost.